INTERACTION BETWEEN TRICHODERMA HARZIANUM AND BIO FERTILIZATION AND THEIR EFFECT ON MICROBIOLOGICAL PROPERTIES IN SOIL RHIZOSPHER OF WHEAT PLANTS . - Suhail , Faris M.; Al-Samarrai, Ismail Khalil (Diyala Agricultural Sciences Journal, 2011)
Bacterial ( Azotobacter chroococcum ) and fungal (Glomus mosseae) fertilizers were used to inoculated the seeds of wheat plants with two levels of NPK in the presence and absent of biopesticied ( Trichoderma harzianum ) to study the interactive effect on the growth of ( A. chroococcum ) , spores number , percentage of roots infection of (G,mosseae ) and colony forming unit of ( T . harzianum ) . The result showed that application of biopesticied (T.harzianum ) markedly increased the cell number of A.chroococcum the percentage of roots infection the spores number and cuf of T.harzianum at all treatment of currant experiment . The highest values of biological properties were achieved with a dual inoculation of ( G. mosseae + A. chroococcum ) . increasing the fertilization recommendation from 50% to 100% NPK markedly decreased the values of all biological properties. The interaction of non pathogenic microorganism in this study were positive and their effect on each other were stimulated .